Factors affecting the quality of profits (empirical study on banks listed on the idx in 2018-2020) - Yolifiandri Yolifiandri; Didin Hikmah Perkasa; Ryani Dhyan Parashakti (Sean Institute, 2024)
Banking companies still support domestic development as institutions with an intermediary function, bringing together parties who need funds and those who have excess funds to encourage economic and industrial development. Therefore, for banking companies to carry out their functions optimally, they must produce good profit growth and maintain the quality of their profits. Maintaining the quality of profits will increase the confidence of investors and other parties in banking companies to invest and collaborate in business for mutual benefit. Therefore, to grow the business and investment climate, good corporate governance is needed to produce good quality profit information. This research aims to analyze how earnings quality is seen from the implementation of Corporate Governance (Institutional et al. Committee, Independent Commissioners), and dividend payments are the main issues of this paper, which are expected to reduce the occurrence of profit manipulation. The population of this research is banking industry companies listed on the Indonesian Stock Exchange for the 2018-2020 period. The research sampling technique that the researcher used was purposive sampling. The analysis techniques that researchers use are multiple regression analysis and descriptive statistics. The data analysis researchers used was with the help of the SPSS 26.00 application.